Enhancing Learning Motivation in Islamic Education through Quizizz: Evidence from a Quasi-Experimental Study - Zahro, Fatimatuz; Fawait, Agus; Sari, Diah Kartika (AL-ISHLAH: Jurnal Pendidikan, 2026)
Research on gamified learning in Islamic education remains limited, particularly studies examining the effect of digital learning media on students’ learning motivation. This study investigated whether Quizizz improves students’ motivation in Islamic Education compared with conventional instruction.A quantitative quasi-experimental design with a nonequivalent control group was employed. The participants were 69 tenth-grade students at SMKN 2 Bondowoso, Indonesia, consisting of 34 students in the experimental group and 35 students in the control group. The experimental group learned Islamic Education using Quizizz, while the control group received conventional instruction. Students’ learning motivation was measured using a validated and reliable 20-item questionnaire based on Keller’s ARCS motivation model. Data were analyzed using descriptive statistics, prerequisite tests, an independent-samples t-test, simple linear regression, and Cohen’s d effect size.The experimental group achieved a higher posttest mean score than the control group (M = 83.09, SD = 8.17 vs. M = 64.29, SD = 8.33). The difference was statistically significant, t(67) = −9.47, p .001, with a very large effect size. Regression analysis also showed that Quizizz had a positive and significant effect on students’ learning motivation, explaining 12.4% of the variance.The findings suggest that Quizizz can enhance students’ learning motivation by creating a more interactive, engaging, and feedback-rich learning environment. Integrating gamified digital media into Islamic Education may support more active and student-centered learning, although further studies with stronger experimental controls and longer intervention periods are recommended.